An analysis of the resonance attenuation in a combustion chamber. (April 2023) - Pla, Benjamín; Bares, Pau; Jiménez, Irina; Guardiola, Carlos; Denia, Francisco D
Resonance in internal combustion engines could represent a limiting factor in spark ignited engines, while constitutes a noise source in compression ignition configurations. The total resonance intensity is a combination between the noise source, for example, type of combustion, and the characteristics of the propagation medium, such as the combustion chamber geometry and the composition of the gases. In this work the in-cylinder resonance attenuation in internal combustion engines during the end of combustion is analyzed and modeled in detail. An approach is proposed to reproduce resonance attenuation evolution over a particular cycle. The method is validated using three different engines with different combustion characteristics. The model is able to predict the effect of the engine size, and it can also be implemented in real time to obtain the optimal window for trapped mass estimation by means of the resonance method.